The Role of Teaching Compounds According to Types of Speech in Constructivism - Karimova Umida (Genius Journals, 2022)
This article is dedicated to compare and analyze the compound words of Uzbek, English, to classify the compounds according to morphological and lexical point of view in constructivism.
Keywords: Morphemically Compound; Composition And Derivation; Conversion; Tragicomic